A longitudinal examination of role overload and work–family conflict: The mediating role of interdomain transitions. (3rd January 2013) - Matthews, Russell A.; Winkel, Doan E.; Wayne, Julie Holliday
Summary Through the lens of boundary theory, we examine whether the relationship between role overload and work–family conflict is explained by the use of interdomain transitions. With a sample of 250 working adults, we examined whether individuals respond to role overload by engaging in interdomain transitions and how the frequency of these transitions influences work–family conflict both concurrently and over time. Results support our expectation that at a given time, interdomain transitions function as an episodic coping mechanism with short‐term costs (greater work–family conflict) and benefits (less role overload). Also, engaging in interdomain transitions was an explanatory variable linking role overload and work–family conflict. We expected that, over time, engaging in interdomain transitions would function as a preventive coping mechanism, serving to reduce role overload. Interestingly though, several of the longitudinal hypotheses were counter to prediction. Our findings provide further evidence for the use of boundary theory in examinations of the work–family interface. Insights on areas within the literature that require further theoretical development are discussed, along with a consideration of the application of emerging methodologies within our empirical designs. Copyright © 2013 John Wiley & Sons, Ltd.